PENTINGNYA MEMAHAMI STRUKTUR BERITA DAN ARTIKEL DI MEDIA MASSA INDONESIA - Kusuma, Adhi; Naufal Fadillah , Muhammad; Afriansyah , Sahrul; Rosita , Ita; Anwar , Noufan; Aprilliyanti , Putri Hani; Azizah , Sayidatul; Shidqin Aliyya, Lisana (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
In the era of fast-paced and easily accessible information, understanding news and articles in the mass media is becoming increasingly important. Mass media in Indonesia has a vital role in conveying information to the public. This article aims to explore the importance of understanding the structure of news and articles in Indonesian mass media as well as understanding the structure used in writing news and articles. Through content analysis from various mass media sources in Indonesia, this study identifies the key elements that form the structure of news and articles. Furthermore, this research also assesses the impact of understanding this structure on the reader's level of confidence and knowledge. The research results show that a deep understanding of the structure of news and articles can improve readers' critical abilities in assessing the reliability and relevance of the information presented.